ANALISIS PENGENALAN SENI RUPA (MEMBUTSIR) MENGGUNAKAN TANAH LIAT PADA KELOMPOK B di RA-AL HIDAYAH - Hidayatullah Hidayatullah; Sry Anita Rachman; Samsul Mujtahidin; Farlina Hardianti (JURNAL ASIMILASI PENDIDIKAN, 2024)
The aim of this research is to find out the benefits of the activity of milling clay and to raise any problems that are obstacles that make this activity reluctant to be carried out in several local schools. The introduction to fine arts (Graining) in group B is the activity of forming objects from soft objects such as clay. At age group B, what we develop is cognitive, namely the stimulus of the child's imagination. From this activity of molding clay, a lot of children's development is stimulated, including cognitive, social emotional development, the development of their art and the use of natural materials as learning media. This research is a descriptive qualitative research with research subjects 12 children in group B and 2 teachers in Ra Al-Hidayah Paok Lombok. Data collection techniques Observation and documentation. The data analysis technique used is data reduction, where the use of clay in introductory fine arts activities is very effective. We have used it, proven that the results on average have developed according to expectations (BSH). This is also supported by documentation in the form of photos during the activity and photos of group B's work.